Pemberdayaan Kelompok Wanita Tani Melalui Program Pengabdian Pelatihan Kompos Mendukung Sustainable Agriculture - Hasna Nadia; Fitrotin Nisak; Hera Kumalasari; Hernika Aulia; Dania Maulinda; Nabila Izzaba Fillard; Bagus Aradea; Bagas Ardiyanto; Sri Edy Satmoko; Angger Adetya Yusuf Putu Suhendy; Reza Noormansyah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Indonesia as an agricultural country rich in natural resources, relies heavily on agriculture to support its economy, especially in Central Java where the majority of the population are farmers. However, many rural areas, such as Tegalrandu village in Srumbung, Magelang, face challenges due to limited agricultural knowledge and resources. This study aims to empower farmers in Tegalrandu by improving their agricultural practices through the use of compost as a sustainable fertilizer. This study uses the Asset Based Community Development (ABCD) methodology, which focuses on local strengths and assets to catalyze community-driven development. Participants included local farmers who were engaged through a series of workshops and hands-on training in compost production using household waste and natural activators. The results showed that farmers successfully produced high-quality compost, leading to improved soil health and crop yields. In addition, the community showed increased knowledge and confidence in sustainable agricultural practices. This study underscores the importance of participatory approaches in agricultural development, highlighting the potential of composting to not only increase crop production but also foster economic resilience among rural farmers. The implications extend beyond local agricultural practices, suggesting that similar empowerment strategies can be applied in other rural contexts to promote sustainability and community development.